Čustva v judovsko-krščanski tradiciji in preseganje dualističnih kartezijanskih binarizmov - pogled krščanske feministične teologije - Furlan-Štante, Nadja (Bogoslovni vestnik, 2025)
Applying the methodology of Christian feminist hermeneutics, the paper first analyses the phenomenon and impact of Cartesian binarism on the understanding and evaluation of emotions, emotionality and women in the metanarratives of Western culture and the Judeo-Christian tradition. Cartesian dualism implies a relationship of separation and domination that is codified and naturalized in culture and characterized by radical exclusion, distance and opposition between domains that are systematically defined as inferior and superior, as (over)ruled and dominated (male/female, rational/emotional, spiritual/material, mind/body, etc.). The paper further argues that there is no uniform dichotomy of male rational and female emotional in the Bible or that the hypothesis of a uniform dichotomy between male rationality and female emotionality does not do justice to the complexity of the biblical narratives and proves this with examples. In the Old Testament, there are several women who embody rationality and action in the pursuit of justice and the well-being of others. Deborah (Judg 4–5), for example, is portrayed as a military leader and mediator between warring nations, indicating her strategic thinking and emotional intelligence. Ruth’s decision to leave her family and join Naomi’s clan (Ruth 1:14-18) also shows her resourcefulness and commitment to her new family. Women like Job’s wife (Job 19:17) or Pharaoh’s daughter (Exodus 2:4-7) show practical wisdom, rational and emotional intelligence in their actions and decisions. Contrary to popular belief that men do not show emotions, there are several men in the Old Testament who show a variety of emotions. David (Ps 13:2), for example, is known for giving free rein to his emotions in the Psalms, expressing sadness, anger and longing. In this context, the Bible emphasises the interplay of emotions, reason and action and questions the rigid dichotomy of man and woman. The stories emphasise the importance of empathy, compassion and understanding in human relationships and show that these qualities are fundamental to the human experience and do not exclude either gender.
Keywords: Cartesian binarisms; Christian feminist theology; čustva; emotions; feminist biblical hermeneutics; feministična biblična hermenevtika; gender stereotypes; kartezijanski binarizmi; krščanska feministična teologija; razum; reason; spolni stereotipi; Sveto pismo; the Bible